Evaluation of Calendula officinalis as an anti-plaque and anti-gingivitis agent - Mayur Sudhakar Khairnar; Babita Pawar; Pramod Parashram Marawar; Ameet Mani (Wolters Kluwer Medknow Publications, 2013)
Background: Calendula officinalis (C. officinalis), commonly known as pot marigold, is a medicinal herb with excellent antimicrobial, wound healing, and anti-inflammatory activity. Aim: To evaluate the efficacy of C. officinalis in reducing dental plaque and gingival inflammation. Materials and Methods: Two hundred and forty patients within the age group of 20-40 years were enrolled in this study with their informed consent. Patients having gingivitis (probing depth (PD) ≤3 mm), with a complaint of bleeding gums were included in this study. Patients with periodontitis PD ≥ 4 mm, desquamative gingivitis, acute necrotizing ulcerative gingivitis (ANUG), smokers under antibiotic coverage, and any other history of systemic diseases or conditions, including pregnancy, were excluded from the study. The subjects were randomly assigned into two groups - test group (n = 120) and control group (n = 120). All the test group patients were advised to dilute 2 ml of tincture of calendula with 6 ml of distilled water and rinse their mouths once in the morning and once in the evening for six months. Similarly, the control group patients were advised to use 8 ml distilled water (placebo) as control mouthwash and rinse mouth twice daily for six months. Clinical parameters like the plaque index (PI), gingival index (GI), sulcus bleeding index (SBI), and oral hygiene index-simplified (OHI-S) were recorded at baseline (first visit), third month (second visit), and sixth month (third visit) by the same operator, to rule out variable results. During the second visit, after recording the clinical parameters, each patient was subjected to undergo a thorough scaling procedure. Patients were instructed to carry out regular routine oral hygiene maintenance without any reinforcement in it. Results: In the absence of scaling (that is, between the first and second visit), the test group showed a statistically significant reduction in the scores of PI, GI, SBI (except OHI-S) (P < 0.05), whereas, the control group showed no reduction in scores when the baseline scores were compared with the third month scores. Also, when scaling was performed during the third month (second visit), there was statistically significant reduction in the scores of all parameters, when the third month scores were compared with the sixth month scores in both groups (P < 0.05), but the test group showed a significantly greater reduction in the PI, GI, SBI, and OHI-S scores compared to those of the control group. Conclusion: Within the limits of this study, it can be concluded that calendula mouthwash is effective in reducing dental plaque and gingivitis adjunctive to scaling.